2015
DOI: 10.1021/acs.macromol.5b01583
|View full text |Cite
|
Sign up to set email alerts
|

Linear Rheology of Supramolecular Polymers Center-Functionalized with Strong Stickers

Abstract: We investigate the linear viscoelastic properties of a series of low polydispersity poly(n-butyl) acrylate chains center-functionalized with a triurea interacting moiety, able to self-associate by six hydrogen bonds. Depending on the molecular weight (M n ) of the side chains, the polymers can self-associate and form supramolecular structures in the melt state. For M n < 40 kg/mol, the polymers form large bundles of parallel rods which relax stress as large colloidal objects. For M n ≥ 40 kg/mol, the self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 28 publications
11
64
0
Order By: Relevance
“…By increasing the molecular weight, the distance between the rods increased, although long‐range order was lost for molecular weights above 20 kg mol −1 . Room temperature rheological data supported this observation, as high molecular weight polymers were found to be viscoelastic liquids …”
Section: Adhesives Based On Hydrogen Bondingmentioning
confidence: 54%
“…By increasing the molecular weight, the distance between the rods increased, although long‐range order was lost for molecular weights above 20 kg mol −1 . Room temperature rheological data supported this observation, as high molecular weight polymers were found to be viscoelastic liquids …”
Section: Adhesives Based On Hydrogen Bondingmentioning
confidence: 54%
“…From an initial analysis it can be observed that the obtained mastercurves for the different PEIs resemble the ones of lightly entangled polymers (32,33) with four polymer-state regions identified by the intersection points between G' and G", as shown in Figure 4 for the polymer D-1.0 and reported in Table II:…”
Section: Effect Of Odpa/dd1 Ratio On the Branched-pei Architecture Anmentioning
confidence: 98%
“…In the literature, the temperature dependence of the viscosity is indeed Arrhenius-like, because the stress relaxation measurements were performed at temperatures far above T g in agreement with our results. hydrogen bonding motifs [5][6][7]59 . The Arrhenius-like temperature dependence of the viscosity is certainly not a unique nor distinctive property of vitrimers as regular polymeric systems also become Arrhenius-like at high temperatures.…”
Section: Soft Matter Accepted Manuscriptmentioning
confidence: 99%